Serum miR-18a: A Potential Marker for Hepatitis B Virus-Related Hepatocellular Carcinoma Screening - Li, Lihua; Guo, Zijan; Wang, Juanhua; Mao, Yong; Gao, Qi (Digestive diseases and sciences, 2012)
Background A lpha-fetoprotein detection is currently mainly used in clinic for diagnosis of primary hepatocellular carcinoma (HCC). However, its sensitivity and specificity are not satisfying. Approximately 60–80 % of patients with HCC have an established background of chronic infection with hepatitis B virus (HBV). Aims To investigate the potential of serum microRNAs (miRNAs) as biomarkers for HBV-related HCC. Methods This study was divided into two phases: firstly, marker (miR-95, miR-18a, miR-10b, miR125a, and miR-378) detection by real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) in sera from HBV patients with HCC ( n = 15) and health subject ( n = 15); and, secondly, marker validation by real-time qRT-PCR on HBV patients with HCC ( n = 86) or hepatitis or cirrhosis ( n = 30), and healthy subject ( n = 45). Results Serum miR-18a was significantly higher in HBV patients with HCC than healthy controls ( p < 0.01); serum miR-378 was significantly lower in HBV patients with HCC compared to healthy control ( p < 0.05). Receiver operating characteristic (ROC) curve analyses suggested that serum miR-18a had significant diagnostic value for HBV-related HCC. MiR-18a yielded an area under the curve (AUC) of ROC of 0.881 with 86.1 % sensitivity and 75.0 % specificity in discriminating HBV-related HCC from healthy controls, and an AUC of ROC of 0.775 with 77.2 % sensitivity and 70.0 % specificity in discriminating HBV-related HCC from chronic hepatitis or cirrhosis. Conclusions Our results suggest that serum miR-18a might serve as a novel and potential noninvasive biomarker for HBV-related HCC screening.